(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Bharati Mukherjee’s novels offer a profound exploration of how women, particularly those navigating the challenges of migration, cultural dislocation, and societal expectations, actively rewrite their destinies. This research paper examines the central theme of self-reinvention and empowerment in Mukherjee’s works, focusing on how her female protagonists such as Dimple in The Tiger’s Daughter, Jasmine in Jasmine, and Tara in Desirable Daughters defy traditional roles and redefine their identities. Through their journeys of cultural negotiation, personal trauma, and emotional upheaval, Mukherjee’s characters emerge as active agents who transform their lives and assert their autonomy in both personal and social realms. This paper argues that the process of rewriting one’s destiny in Mukherjee’s novels is not only a personal act of liberation but also a political one, where women challenge patriarchal norms and societal boundaries. By analyzing the transformative experiences of Mukherjee’s protagonists, the research highlights the feminist dimensions of her works, offering a critical examination of how women in the diaspora resist and reshape the narratives that seek to limit them.